Psychoanaliza dzieci według Melanii Klein - Szałek, Piotr (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2004)
Participants of polemics connected with the psychotherapeutic aspect of psychoanalysis, discuss the most often about technique. Controversies considerable relating to psychological theory and philosophy, lying at bases of this technique, are treated as secondary. This approach creates conflicting directives of therapeutic technique, forges its ethical dimension and description of psychical life of individual, introduces in the area of culture notions and phenomena not dependent on the social control. Threats resulting from these should be counteracted by psychotherapist's theoretical and philosophical reflection.